Gambaran Pelayananan Kesehatan Ibu dan Anak di UPTD Pusat Kesehatan Masyarakat - Pricilia Hansun; Marnex W. Berhimpong; Agusteivi A. J. Telew (Yayasan Syalom Cipta Sumikolah, 2025)
This study aims to provide an overview of maternal and child healthcare services available at the Ratahan Subdistrict Health Center (Puskesmas) in Southeast Minahasa Regency. The background of this research is the persistently high maternal and infant mortality rates in the region, which indicate that the quality of existing healthcare services has not yet met optimal standards. A descriptive method with a qualitative approach was employed, with data collected through interviews and direct observations at the local health center. The findings reveal that the maternal and child healthcare services at Ratahan Health Center continue to face several challenges. These include inefficiencies in service delivery time, healthcare costs that are not fully affordable for the community, and limited supporting facilities and infrastructure. Community complaints regarding long waiting times and a shortage of medical personnel also contribute to the decline in service quality. The results of this study are expected to serve as input for improving maternal and child healthcare services at the community health center level and to contribute to the advancement of public health science.